Upaya Orang Tua Untuk Membentuk Kebiasaan Positif dalam Penggunaan Internet Di Kalangan Generasi Z di Desa Balimbingan Kecamatan Tanah Jawa - Wahyuni, Rifa; Yusnadi (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The rapid expansion of the internet in rural areas presents both opportunities and challenges for Generation Z, necessitating parental involvement in fostering positive internet usage habits. This study aims to describe the level of parental effort in shaping positive internet usage habits among Generation Z in Balimbingan Village, Tanah Jawa District. A descriptive quantitative approach was employed, involving a population of 778 families and a sample of 89 parents selected via simple random sampling. Data were collected using a Likert-scale questionnaire comprising 27 valid items and analyzed using descriptive statistics. The results indicate that the level of parental effort falls into the "moderate" category, with an average score of 50.3%. Regarding specific indicators, parent-child communication scored the highest (56%), followed by the regulation of internet usage time (50%), parental role modeling (49%), and supervision of internet usage (46.3%). These findings suggest that while parents are aware of the need to guide internet usage, implementation remains suboptimal due to constraints such as limited time, digital literacy, and easy internet access. The study concludes that there is a need to strengthen digital literacy and implement digital parenting education programs to enhance the effectiveness of parental guidance in fostering positive internet usage habits among Generation Z